Determinants of Midwife Compliance in the Recording and Reporting of Maternal and Child Health Services - Maryati; Yuly Peristiowati; Katmini (Journal for Quality in Public Health, 2022)
The note and report MCH services are part of the regular instrumentation for assess health status and degrees health something areas, especially in several target communities such as groups of pregnant women, infants and toddlers which are the core and main variables of the standard of the basic health care system. The urgency of the reporting system, recording and sending reports on time related to maternal and child health data is the gold standard for achieving a fast, accurate service system and prioritizing a valid and credible database so that every occur problem could detected as early as possible and get good handling. Studies This literature review aims to determine the determinants of midwife compliance in recording and reporting MCH services, by searching a database of articles on midwife compliance in recording and reporting MCH services and selecting based on criteria and the final results of finding 10 articles. The inclusion criteria used were journals in English and Indonesian, available in full text, and related to the topic of midwife compliance in recording and reporting MCH services. The exclusion criteria in the preparation of this article are articles that only provide abstracts and are not in English and Indonesian. The results of the literature review show that the compliance of midwives in recording and reporting MCH services is determined by several factors, such as; education, consistency, form availability facilities, workload, motivation, supervision, perception, knowledge and attitude, years of service, responsibility, reward, desire, persist with the job position, complete documents, good support from the leadership, good support from colleagues work. It is recommended to the Puskesmas as the person in charge of the area to further complete the facilities to increase the motivation of midwives and support the success of the program recording MCH reporting.